PENGARUH KESEJAHTERAAN DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN PABRIK ARANG DI PT. KNI STB - Riskiatin Riskiatin; Agusti Agusti; Miftahus Surur (LPPM Politeknik Pratama, 2025)
Employee welfare determines the level of success of a company to grow and develop. The purpose of this study is to determine the effect of welfare and work motivation on employee performance. The data collection techniques used in this study are questionnaires and interviews. The data analysis method used multiple linear regression. The research results showed the following: The calculated F value was 6.114, while the F table result in the distribution table with a 5% error rate was 2.96. This means that the calculated F value is greater than the table F value (6.114 > 3.32), so H0 is rejected or Ha is accepted, which can be interpreted as meaning that, overall, the variables of well-being and motivation have a significant influence on employee performance. The t-test for the welfare variable (X1) yielded a calculated t-value of 3.769 with a significance level of 0.001. Since the calculated t-value is greater than the table t-value (3.769 > 2.042), H0 is rejected and H1 is accepted, which means that the independent variable has a partial effect. In other words, the first hypothesis in this study states that the welfare variable influences employee performance. The t-test for the work motivation variable (X2) yielded a t-value of 4.756 with a significance level of 0.000. Since the t-value is greater than the critical t-value (4.756 > 2.042), H0 is rejected and H2 is accepted, indicating that the independent variable has a partial effect. In other words, the second hypothesis in this study states that the work motivation variable influences employee performance.